Legal barriers to adaptive coastal management at a coastal erosion hotspot in Florianópolis, Brazil. (May 2021) - Frohlich, Miguel F.; Smith, Timothy F.; Fidelman, Pedro; Baldwin, Claudia; Jacobson, Chris; Carter, R.W. (Bill)
Abstract: Adaptive management has long been promulgated as an appropriate approach to address the complexity and dynamics of coastal social-ecological systems. However, examples of successful implementation of this approach are still scarce. Law may be a factor hindering adaptive management, particularly when legal provisions are too rigid to enable change. Drawing on the management experience of Armação Beach (a coastal erosion hotspot in the Municipality of Florianópolis, State of Santa Catarina, Brazil), this paper: (a) analyses how adaptive management has been used for coastal management in the selected study area and its applicable legal framework; and (b) identifies legal barriers to adaptive coastal management. Document analysis and semi-structured interviews with 27 participants were undertaken. An inductive thematic coding strategy was adopted to analyse interview data. Interpretation of results shows that coastal management in Florianópolis is yet to follow the structured and iterative learning process of adaptive management. Vague, imprecise, and generic legal provisions have contributed to reactive coastal management. In the context of open-ended legislation, government entities have used their legal discretion to avoid making coastal management plans, and short-term defence strategies to manage coastal erosion have proliferated in response to crisis situations. The paper highlights the importance of seeking the right balance between legal certainty and legal flexibility, providing an entry point to further research and legal reform discussions in the field of adaptive coastal management.